The Effect of a Combination of Oxytocin Massage and Music Therapy on Breast Milk Production and Breastfeeding Self Efficacy in Primipara Post Partum Mothers - Sri Wulandari; Mira Triharini; Sylvia Dwi Wahyuni (Pediomaternal Nursing Journal, 2020)
ABSTRACTIntroduction: exclusive breastfeeding. Factors that affect mothers not to give breast milk to babies, including the condition of mothers who are stressed, lack of confidence can cause the production of breast milk not smooth. The aim of this study was to study the combination of oxytocin therapy and music therapy in breast milk production and breastfeeding self-efficacy in postpartum mothers.Method: The study design used Quasy Experiment with a pre-posttest design. The population of mothers after childbirth who worked in the Kalijudan Health Center area, Surabaya. The sample used was 80 respondents, divided into 2 groups, 40 intervention groups and 40 control groups with purposive sampling. The independent variable is a combination of oxytocin therapy and music therapy. The dependent variable is breast milk production and breastfeeding self efficacy. The instrument used was a questionnaire breastfeeding production and breastfeeding self efficacy was validated and reliably. The research data were analyzed by the Wilcoxon Signed Rank Test and the Mann Withney test.Result: the results showed that there was a combination of oxytocin therapy and music therapy in breast milk production (p = 0,000) and breastfeeding self efficacy (p = 0,000) in the treatment group. There was a significant difference between the control and treatment groups in breast milk production (p = 0,000) and breastfeeding self efficacy (p = 0,000). Conclussion: the combined effect of oxytocin massage and music therapy effectively increases breast milk production and the efficacy of caring for it. Keyword: Oxytocin Massage, music therapy, ASI production, Breastfeeding Self Efficacy.